Teaching And Learning Process In Virtual Higher Education: A Literature Review (Journal of Namibian Studies : History Politics Culture, 2023)
The teaching-learning process in virtual education during the last three years has taken a 360 degree turn because of the Covid-19 pandemic. In this period, the education sector in its various levels moved from the face-to-face stage to the virtual stage with the use of different tools that allow both the teacher and the student to carry out this process. The objective was to identify the current state of theoretical and methodological development of teaching and learning in virtual higher education. For this purpose, bibliometric analysis and an analytical review of the literature were conducted. As a result, it was found that for the last 3 years, researchers have given greater importance to this topic in their studies; among the countries that have had the most participation in this field of study are Spain, Colombia, Ecuador, and Peru; the types of documents most written were articles, followed by conference papers; and the areas that have given greater importance to this topic are the social sciences and computer sciences; in addition, the advances of technology in the education sector and the applications in developed countries stand out. Finally, it was concluded that although technology is indeed a useful tool for the educational sector, those who wish to use it must consider the factors that affect its good performance.